Implementation of Carbon Emission Disclosure on Market Reaction with Green Investment as a Mediating Variable in Companies Listed on the Indonesian Carbon Exchange (IDX Carbon) - Rico Nur Ilham; Muammar Khaddafi; Mangasi Sinurat; Irada Sinta; Irshad Ahmad Reshi (Politeknik Siber Cerdika Internasional, 2025)
Background: The Indonesian Carbon Exchange (IDX Carbon) has emerged as a critical mechanism for carbon trading, introducing carbon units as securities rather than commodities. Despite this development, challenges remain in ensuring the integrity of carbon markets, including issues of double counting, manipulation of carbon unit measurements, and regulatory gaps. Objective: This study aims to examine the implementation of Carbon Emission Disclosure on Market Reaction with Green Investment as a mediating variable in companies listed on IDX Carbon. Methods: This study employed a quantitative research approach using SmartPLS with PLS-SEM. Hypothesis testing applied a t-statistic threshold of 1.96 and a significance level of α = 5% (p-value < 0.05). Results: All variables had Cronbach's Alpha values above 0.95 and AVE values above 0.66, indicating high reliability and validity. The R² value of Green Investment (Z) was 0.983 and Market Reaction (Y) was 0.925, indicating strong predictive relevance. Hypothesis testing revealed: (1) Green Investment significantly affects Market Reaction (t = 9.422, p = 0.000); (2) Carbon Emission Disclosure significantly affects Green Investment (t = 6.017, p = 0.000); (3) Carbon Emission Disclosure significantly affects Market Reaction (t = 2.655, p = 0.000); and (4) Carbon Emission Disclosure significantly affects Market Reaction through Green Investment as a mediating variable (t = 8.672, p = 0.000). All four hypotheses were accepted. Conclusion: Carbon Emission Disclosure has a significant direct effect on both Green Investment and Market Reaction in IDX Carbon-listed companies. Green Investment also serves as a significant mediating variable between Carbon Emission Disclosure and Market Reaction, highlighting the importance of transparent carbon emission reporting in supporting sustainable finance in Indonesia.